Workload, Work-Life Balance, and Job Satisfaction: Their Impact on Nurse Performance at Goenawan Partowidigdo Pulmonology Hospital - Fauzi, Izmal; Muharram, Hari; Hadiyat, Yayan; Arismiadi, Mujtahid (International Journal Administration, Business & Organization, 2025)
This study explores the relationship between workload and work-life balance with nurses' performance, with job satisfaction as a mediating factor, at Goenawan Partowidigdo Pulmonology Hospital in Bogor. The study is based on the demands for providing optimal patient care, which requires optimal nurse performance. However, there are still suboptimal work outcomes, such as patient safety incidents involving nurses, where nurse performance can be influenced by several factors, including workload, work-life balance, and job satisfaction, which serves as a mediating variable in this relationship. A quantitative research design was applied using a survey method and total population sampling. Of the 171 nurses, 140 completed the questionnaire. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The results show that workload does not significantly affect job satisfaction, while work-life balance has a positive and significant effect. Additionally, job satisfaction was found to have no significant effect on nurses' performance. In contrast, workload shows a marginally significant positive impact on performance, while work-life balance has no direct influence. Neither workload nor work-life balance affects performance indirectly through job satisfaction. The implications of this research suggest that improving nurse performance can be achieved through fair workload distribution and better workload management. Furthermore, policies that support nurses in balancing work and personal life are also important. Although work-life balance does not have a direct impact on performance, such policies still contribute to job satisfaction, which in turn can improve the quality of care and support overall nurse performance improvement.